Thermal insulation lightweight concrete and preparation method thereof
By adding anti-floating agent to lightweight concrete, the problem of poor dispersion of EPS particles is solved, the structural stability and mechanical properties are significantly improved, and the flame retardant properties are enhanced.
Patent Information
- Application Number
- CN202411931704.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The dispersion of EPS particles in existing lightweight concretes is poor, resulting in uneven density and reduced structural stability, affecting the mechanical properties.
The lightweight concrete is added to the lightweight concrete, and the colloid is formed in water and negative charge is provided to enhance the interaction force between the EPS particles and the concrete matrix, inhibit the agglomeration and floating of the EPS particles, and improve their dispersion.
The structural stability and mechanical properties of lightweight concrete are significantly improved, ensuring its uniformity and thermal insulation properties, while enhancing flame retardant properties.
Smart Images

Figure BDA0005210492540000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building thermal insulation materials, and in particular to a thermal insulation lightweight concrete and a preparation method thereof. Background Art
[0002] With the continuous development of my country's construction industry, more and more construction projects have incorporated the concept of energy conservation and environmental protection. Insulation technology plays a vital role in building energy conservation, and lightweight concrete has a lower thermal conductivity than ordinary concrete, which also makes it an ideal insulation material in the construction field.
[0003] In the prior art, in order to reduce the specific gravity of concrete, lightweight concrete is generally achieved by adding lightweight aggregate. EPS (polystyrene foam) particles have the advantages of light weight and low thermal conductivity. Adding them to concrete as lightweight aggregate can well achieve lightweight concrete and obtain lightweight concrete with good thermal insulation performance. However, EPS particles are hydrophobic organic materials and have poor compatibility with inorganic substances such as concrete. In addition, EPS particles have a small density and are easy to float during the mixing and molding process. These phenomena can easily lead to the difficulty of EPS particles being evenly dispersed in lightweight concrete, resulting in uneven density of lightweight concrete, resulting in reduced structural stability of lightweight concrete, and causing a certain impact on the mechanical properties of lightweight concrete.
[0004] Therefore, in order to further enhance the mechanical properties of lightweight concrete, it is necessary to further improve the dispersibility of EPS particles in lightweight concrete. Summary of the invention
[0005] In order to further improve the dispersibility of EPS particles in lightweight concrete, the present application provides a thermal insulation lightweight concrete and a preparation method thereof. The present application effectively inhibits the agglomeration and floating of EPS particles in the concrete by adding an anti-floating agent to the lightweight concrete, effectively improves the dispersibility of EPS particles in the concrete, ensures the uniformity and quality of the lightweight concrete, and thus improves the structural stability and mechanical properties of the lightweight concrete.
[0006] In the first aspect, the thermal insulation lightweight concrete provided in the present application adopts the following technical solution:
[0007] A thermal insulation lightweight concrete comprises the following components in parts by weight: 340-360 parts of cement, 85-95 parts of fly ash, 20-40 parts of rice husk ash, 250-270 parts of sand, 12-16 parts of EPS particles, 9-12 parts of expanded perlite particles, 5-8 parts of sepiolite fibers, 8-12 parts of anti-floating agent, 7-9 parts of water reducing agent, and 165-180 parts of water, wherein the anti-floating agent is prepared by mixing corn starch, starch phosphate, polyethylene oxide and sodium lignin sulfonate.
[0008] Through the above technical scheme, by adding a specific proportion of anti-floating agent, the thermal insulation lightweight concrete of the present invention significantly improves its structural stability and mechanical properties while maintaining good thermal insulation performance. The addition of anti-floating agent not only improves the dispersibility of EPS particles, but also enhances the compatibility between EPS particles and concrete matrix through its unique chemical composition, thereby effectively preventing the agglomeration and floating of EPS particles. Specifically, the anti-floating agent can form a colloid in water and provide a negative charge, which well enhances the interaction between EPS particles and concrete, thereby improving the stability of EPS particles in concrete, significantly reducing the floating or agglomeration of EPS particles, and promoting the stable dispersion of EPS particles. The hydrophilic group in the anti-floating agent interacts with the hydrophobic group on the surface of the EPS particles, reducing the surface tension of the EPS particles, further improving the bonding force between the EPS particles and concrete, and further enhancing the dispersibility of the EPS particles in the concrete, promoting the uniform distribution of the EPS particles, thereby ensuring the uniformity and thermal insulation of the thermal insulation lightweight concrete.
[0009] At the same time, the thermal insulation lightweight concrete of the present application also further enhances the bonding strength between EPS particles, expanded perlite particles and concrete by adding sepiolite fiber and rice husk ash, and interacts with the anti-floating agent through the mutual cooperation of sepiolite fiber and rice husk ash, reduces the floating of lightweight aggregate, further improves the structural stability and mechanical properties of concrete, and also improves the flame retardant performance of concrete. Specifically, rice husk ash can effectively fill the micropores and gaps between EPS particles, expanded perlite particles and concrete matrix through volcanic ash active reaction, and cooperates with anti-floating agent to optimize the interface transition period inside concrete from a microscopic level, while sepiolite fiber runs through the concrete through toughening and bridging effects, and the gel formed by rice husk ash and anti-floating agent is more evenly distributed around the fiber, and cooperates with each other to form a stronger interface bond, thereby enhancing the overall structure of concrete.
[0010] Furthermore, the mixing mass ratio of the corn starch, starch phosphate, polyethylene oxide and sodium lignin sulfonate is 1: (0.5-0.7): (0.3-0.5): (0.1-0.2).
[0011] Furthermore, the mixing mass ratio of the corn starch, starch phosphate, polyethylene oxide and sodium lignin sulfonate is 1:0.6:0.4:0.15.
[0012] Furthermore, the preparation method of the anti-floating agent comprises: adding corn starch to 10 times the volume of water at 50-60° C., stirring evenly, then adding starch phosphate, polyethylene oxide and sodium lignin sulfonate in sequence, continuing stirring for 10-20 minutes, and drying to obtain the anti-floating agent.
[0013] Through the above technical scheme and the preparation method, an anti-floating agent with stable performance can be obtained. Such an anti-floating agent can effectively play its role in concrete, inhibit the floating or agglomeration of lightweight aggregates such as EPS particles, etc., thereby ensuring the uniformity and stability of thermal insulation lightweight concrete.
[0014] Furthermore, the mass ratio of the EPS particles to the expanded perlite particles is 15:10.
[0015] Through the above technical solution, by selecting a specific ratio of EPS particles and expanded perlite particles, it is possible to ensure that lightweight concrete maintains good thermal insulation performance while further improving its structural stability and mechanical properties. In concrete, the uniform distribution of EPS particles and expanded perlite particles helps to form a more uniform pore structure, thereby improving the thermal insulation performance of concrete. This application can further optimize the density and strength of concrete by further controlling the ratio of EPS particles and expanded perlite particles, so that the lightweight concrete of this application has sufficient structural strength while meeting the thermal insulation requirements.
[0016] Furthermore, the fineness modulus of the sand is 2.6 to 2.8.
[0017] Through the above technical scheme, by optimizing the particle size distribution of EPS particles and expanded perlite particles, as well as the fineness modulus of sand, and by optimizing the mass ratio of EPS particles and expanded perlite particles, not only the uniformity of concrete is further ensured, but also the aggregate structure of concrete can be further optimized, the structural stability of concrete can be improved, and the mechanical strength of concrete can be further enhanced.
[0018] Furthermore, the preparation method of the rice husk ash comprises: calcining rice husk at 450-500° C. for 30-45 minutes, and then grinding for 30-35 minutes to obtain rice husk ash.
[0019] Furthermore, the rice husk ash is modified rice husk ash, and the preparation method of the modified rice husk ash comprises the following steps:
[0020] Step s1: completely immerse the rice husk ash in a 2 mol / L sodium hydroxide solution, then treat it at a temperature of 90 to 100° C. for 1 to 1.2 hours, and then take it out and dry it;
[0021] Step s2: at 120-130° C., 100 parts of dried rice husk ash are dispersed again in 5-10 times the volume of water, 8-12 parts of ammonium dihydrogen phosphate and 2-3 parts of polyethyleneimine are added, mixed and stirred for 1-2 hours, 10-15 parts of urea are added and stirring is continued for 1-2 hours, filtered, and dried at 100-120° C. to obtain modified rice husk ash.
[0022] Through the above technical scheme, the rice husk ash is modified by using sodium hydroxide, ammonium dihydrogen phosphate, polyethyleneimine and urea, and the rice husk ash is modified by surface activation and active site optimization, flame retardancy optimization, interface bonding and microstructure optimization, etc., so as to further improve the activity, dispersibility and flame retardancy of the rice husk ash, enhance the bonding ability of the rice husk ash with concrete, and further enhance the structural stability and mechanical properties of the concrete. Specifically, through the alkaline excitation of NaOH, impurities on the surface of the rice husk ash are removed, the surface reactive sites of the rice husk ash are increased, and the surface reactive activity of the rice husk ash is improved, so that the subsequent ammonium dihydrogen phosphate, polyethyleneimine and urea can be more effectively adsorbed on these active sites to form an effective combination. The combined action of ammonium dihydrogen phosphate, polyethyleneimine and urea on the rice husk ash can synergistically improve the interfacial bonding and flame retardancy of the rice husk ash, so that the concrete has better flame retardancy and mechanical properties.
[0023] Furthermore, the mass ratio of the rice husk ash to the sepiolite fiber is 30:7.
[0024] Through the above technical scheme, because rice husk ash has good flame retardant properties, it can form a dense coke layer under high temperature conditions to play a role in heat insulation and oxygen isolation. The sepiolite fiber itself also has certain heat resistance and chemical stability, and can maintain structural integrity in a high temperature environment. The combination of the two not only improves the stability of concrete, but also unexpectedly improves the flame retardant properties of concrete.
[0025] In a second aspect, the present application provides a method for preparing thermal insulation lightweight concrete using the following technical solution:
[0026] A method for preparing thermal insulation lightweight concrete comprises the following steps:
[0027] Step 1: Take 20% to 25% of the formula amount of water, add anti-floating agent and stir evenly, then add EPS particles and expanded perlite particles, continue to stir evenly, then add rice husk ash and sepiolite fiber and stir evenly to obtain material 1; take cement, fly ash and sand and stir evenly to obtain material 2; take the remaining water, add water reducing agent and stir evenly to obtain material 3;
[0028] Step 2: First mix material 2 and material 3 and stir evenly, then add material 1 and continue stirring evenly to obtain thermal insulation lightweight concrete.
[0029] Through the above preparation method, it is possible to ensure that the components are mixed evenly, especially to ensure good dispersion of EPS particles and expanded perlite particles in concrete, thereby preparing lightweight concrete with good thermal insulation and mechanical properties. The preparation method of the present application is easy to operate, suitable for industrial production, and has good application prospects.
[0030] In summary, the present application includes at least one of the following beneficial technical effects:
[0031] 1. The use of anti-floating agents promotes the uniform distribution of EPS particles and expanded perlite particles, forming a more uniform pore structure and effectively improving the thermal insulation performance of concrete.
[0032] 2. By optimizing the ratio of EPS particles and expanded perlite particles, as well as the fineness modulus of sand, the aggregate structure of concrete is optimized, thereby improving the structural stability and mechanical strength of concrete.
[0033] 3. The flame retardant properties of concrete are improved by modifying rice husk ash. The combined use of rice husk ash and sepiolite fiber not only further improves the stability of concrete, but also further enhances the flame retardant properties of concrete. DETAILED DESCRIPTION
[0034] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0035] Preparation Example 1
[0036] A method for preparing an anti-floating agent comprises: adding 1 kg of corn starch to 10 times the volume of water at 55°C, stirring evenly, then sequentially adding 0.6 kg of starch phosphate, 0.4 kg of polyethylene oxide and 0.15 kg of sodium lignin sulfonate, continuing stirring for 15 minutes, and drying to obtain the anti-floating agent.
[0037] Among them, corn starch is pregelatinized corn starch purchased from Shandong Xuguang Chemical Co., Ltd.; starch phosphate is phosphorylated distarch phosphate purchased from Shandong Aicai Biotechnology Co., Ltd.; polyethylene oxide is American Dow polyethylene oxide PEO purchased from Shanghai Youdao Oba Chemical Co., Ltd.; sodium lignin sulfonate is sodium lignin purchased from Jinan Runyue Chemical Co., Ltd.
[0038] Preparation Example 2
[0039] A method for preparing an anti-floating agent, which is different from Preparation Example 1, comprises: adding 1 kg of corn starch to 10 times the volume of water at 50° C., stirring evenly, then adding 0.5 kg of starch phosphate, 0.5 kg of polyethylene oxide and 0.1 kg of sodium lignin sulfonate in sequence, continuing to stir for 20 minutes, and drying to obtain an anti-floating agent.
[0040] Preparation Example 3
[0041] A method for preparing an anti-floating agent, which is different from Preparation Example 1, comprises: adding 1 kg of corn starch to 10 times the volume of water at 60° C., stirring evenly, then adding 0.7 kg of starch phosphate, 0.3 kg of polyethylene oxide and 0.2 kg of sodium lignin sulfonate in sequence, continuing to stir for 10 minutes, and drying to obtain an anti-floating agent.
[0042] Preparation Example 4
[0043] A method for preparing an anti-floating agent, which is different from Preparation Example 1 in that starch phosphate is replaced by starch acetate in an equal amount, and the remaining steps are the same.
[0044] Among them, acetate starch is acetate starch E1420 purchased from Guangdong Mingcheng Biotechnology Co., Ltd.
[0045] Preparation Example 5
[0046] A method for preparing an anti-floating agent, which is different from Preparation Example 1 in that an equal amount of polyethylene oxide is replaced by sodium polyacrylate, and the remaining steps are the same.
[0047] Among them, sodium polyacrylate was purchased from Guangdong Mingcheng Biotechnology Co., Ltd.
[0048] Preparation Example 6
[0049] A method for preparing an anti-floating agent, which is different from Preparation Example 1 in that an equal amount of sodium lignin sulfonate is replaced by sodium carboxymethyl cellulose, and the remaining steps are the same.
[0050] Among them, sodium carboxymethyl cellulose was purchased from Guangdong Mingcheng Biotechnology Co., Ltd.
[0051] Preparation Example 7
[0052] A method for preparing rice husk ash comprises: taking dried rice husk and calcining it at 450°C for 15 minutes, then heating it to 500°C within 10 minutes, and continuing to calcine it for 15 minutes, then grinding the calcined material for 35 minutes, and passing it through a 200-mesh sieve to obtain rice husk ash.
[0053] Preparation Example 8
[0054] A method for preparing modified rice husk ash comprises the following steps:
[0055] Step s1: The rice husk ash obtained in Preparation Example 7 is completely immersed in a 2 mol / L sodium hydroxide solution, then treated at a temperature of 90° C. for 1 h, and then taken out and dried.
[0056] Step s2: at 120°C, 10 kg of dried rice husk ash is dispersed again in 8 times the volume of water, 1.2 kg of ammonium dihydrogen phosphate and 0.2 kg of polyethyleneimine are added, mixed and stirred for 2 hours, 1 kg of urea is added and stirring is continued for 2 hours, filtered, and dried at 100°C to obtain modified rice husk ash.
[0057] Among them, diammonium phosphate was purchased from Guangdong Mingcheng Biotechnology Co., Ltd.; polyethyleneimine was purchased from Maoming Xiongda Chemical Co., Ltd., with an average molecular weight of 1800; urea was purchased from Foshan Guangzheng Chemical Co., Ltd., with product number GZ20200226.
[0058] Preparation Example 9
[0059] A method for preparing modified rice husk ash, which is different from Preparation Example 8, comprises the following steps:
[0060] Step s1: The rice husk ash obtained in Preparation Example 7 is completely immersed in a 2 mol / L sodium hydroxide solution, then treated at a temperature of 98° C. for 1.2 h, and then taken out and dried.
[0061] Step s2: at 130°C, 10 kg of dried rice husk ash was dispersed again in 5 times the volume of water, 0.8 kg of diammonium phosphate and 0.3 kg of polyethyleneimine were added, mixed and stirred for 1.5 hours, 1.5 kg of urea was added and continued to stir for 1.5 hours, filtered, and dried at 105°C to obtain modified rice husk ash.
[0062] Preparation Example 10
[0063] A method for preparing modified rice husk ash, which is different from Preparation Example 8 in that an equal amount of diammonium phosphate is replaced by ammonium polyphosphate, and the remaining steps are the same.
[0064] Preparation Example 11
[0065] A method for preparing modified rice husk ash, which is different from Preparation Example 8 in that an equal amount of polyethyleneimine is replaced with sodium polyacrylate, and the remaining steps are the same.
[0066] Among them, ammonium polyphosphate is ammonium polyphosphate APP purchased from Guangzhou Shanghe Chemical Technology Co., Ltd.
[0067] Preparation Example 12
[0068] A method for preparing modified rice husk ash is different from Preparation Example 8 in that an equal amount of urea is replaced by tetrakishydroxymethylphosphonium chloride, and the remaining steps are the same.
[0069] Among them, tetrakis hydroxymethyl phosphonium chloride was purchased from Wuhan Chengtian Fine Chemical Co., Ltd.
[0070] Example 1
[0071] A thermal insulation lightweight concrete includes 3.5kg of cement, 0.9kg of fly ash, 0.3kg of rice husk ash, 2.6kg of sand, 0.15kg of EPS particles, 0.1kg of expanded perlite particles, 0.07kg of sepiolite fiber, 0.1kg of anti-floating agent, 0.08kg of water reducing agent, and 1.72kg of water.
[0072] Among them, the cement is Southern Cement P·O42.5, which was purchased from Hunan Xindingli New Materials Technology Co., Ltd.
[0073] Among them, the fly ash is first-grade fly ash with a particle size of 200 meshes.
[0074] Among them, rice husk ash is prepared by Preparation Example 7.
[0075] Among them, the sand is river sand with a fineness modulus of 2.73.
[0076] Among them, EPS particles were purchased from Henan Jiufeng Water Treatment Co., Ltd. and are 5-8mm lightweight polystyrene round particles.
[0077] Among them, the expanded perlite particles were purchased from Shenyang Jiazhikai Insulation Materials Co., Ltd. and are 2-4 mm expanded perlite particles.
[0078] Among them, the sepiolite fiber was purchased from Shijiazhuang Mayue Building Materials Co., Ltd. with a specification of 1-4mm.
[0079] Wherein, the anti-floating agent is prepared by Preparation Example 1.
[0080] Among them, the water reducer is the polycarboxylic acid water reducer of Wuhan Runxingyuan Technology Co., Ltd.
[0081] The method for preparing the thermal insulation lightweight concrete comprises the following steps:
[0082] Step 1: Take 24% of the formula amount of water, add the anti-floating agent obtained in Preparation Example 1 and stir evenly, then add EPS particles and expanded perlite particles, continue to stir evenly, then add rice husk ash and sepiolite fiber and stir evenly to obtain material 1.
[0083] Step 2: Mix cement, fly ash and sand evenly to obtain material 2.
[0084] Step 3: Take the remaining water, add the water reducer and stir evenly to obtain material 3.
[0085] Step 4: First mix material 2 and material 3 and stir evenly, then add material 1 and continue stirring evenly to obtain thermal insulation lightweight concrete.
[0086] Example 2
[0087] A thermal insulation lightweight concrete, which is different from Example 1 in that it includes 3.4kg cement, 0.85kg fly ash, 0.2kg rice husk ash, 2.5kg sand, 0.12kg EPS particles, 0.09kg expanded perlite particles, 0.05kg sepiolite fiber, 0.08kg anti-floating agent, 0.07kg water reducer, and 1.65kg water.
[0088] Among them, the anti-floating agent is prepared by Preparation Example 2.
[0089] The method for preparing the thermal insulation lightweight concrete comprises the following steps:
[0090] Step 1: Take 20% of the formula amount of water, add the anti-floating agent obtained in Preparation Example 1 and stir evenly, then add EPS particles and expanded perlite particles, continue to stir evenly, then add rice husk ash and sepiolite fiber and stir evenly to obtain material 1.
[0091] Step 2: Mix cement, fly ash and sand evenly to obtain material 2.
[0092] Step 3: Take the remaining water, add the water reducer and stir evenly to obtain material 3.
[0093] Step 4: First mix material 2 and material 3 and stir evenly, then add material 1 and continue stirring evenly to obtain thermal insulation lightweight concrete.
[0094] Example 3
[0095] A thermal insulation lightweight concrete, which is different from Example 1 in that it includes 3.6kg of cement, 0.95kg of fly ash, 0.4kg of rice husk ash, 2.7kg of sand, 0.16kg of EPS particles, 0.12kg of expanded perlite particles, 0.08kg of sepiolite fiber, 0.12kg of anti-floating agent, 0.09kg of water reducer, and 1.8kg of water.
[0096] Among them, the anti-floating agent is prepared by Preparation Example 3.
[0097] The method for preparing the thermal insulation lightweight concrete comprises the following steps:
[0098] Step 1: Take 25% of the formula amount of water, add the anti-floating agent obtained in Preparation Example 1 and stir evenly, then add EPS particles and expanded perlite particles, continue to stir evenly, then add rice husk ash and sepiolite fiber and stir evenly to obtain material 1.
[0099] Step 2: Mix cement, fly ash and sand evenly to obtain material 2.
[0100] Step 3: Take the remaining water, add the water reducer and stir evenly to obtain material 3.
[0101] Step 4: First mix material 2 and material 3 and stir evenly, then add material 1 and continue stirring evenly to obtain thermal insulation lightweight concrete.
[0102] Example 4
[0103] A thermal insulation lightweight concrete, which is different from Example 1 in that rice husk ash is prepared by Preparation Example 8.
[0104] Example 5
[0105] A thermal insulation lightweight concrete, which is different from Example 1 in that rice husk ash is prepared by Preparation Example 9.
[0106] Example 6
[0107] A thermal insulation lightweight concrete, which is different from Example 1 in that rice husk ash is prepared by Preparation Example 10.
[0108] Example 7
[0109] A thermal insulation lightweight concrete, which is different from Example 1 in that rice husk ash is prepared by Preparation Example 11.
[0110] Example 8
[0111] A thermal insulation lightweight concrete, which is different from Example 1 in that rice husk ash is prepared by Preparation Example 12.
[0112] Comparative Example 1
[0113] A thermal insulation lightweight concrete, which is different from Example 1 in that the anti-floating agent is prepared by Preparation Example 4.
[0114] Comparative Example 2
[0115] A thermal insulation lightweight concrete, which is different from Example 1 in that the anti-floating agent is prepared by Preparation Example 5.
[0116] Comparative Example 3
[0117] A thermal insulation lightweight concrete, which is different from Example 1 in that the anti-floating agent is prepared by Preparation Example 6.
[0118] Comparative Example 4
[0119] A thermal insulation lightweight concrete, which is different from Example 1 in that the sepiolite fibers are replaced by glass fibers in equal amounts.
[0120] Among them, the glass fiber is chopped glass fiber purchased from Yaoyang Mineral Products Processing Plant in Lingshou County, with a specification of 1-4mm.
[0121] Performance Testing
[0122] Mechanical properties: Insulating lightweight concrete slurries of Examples 1 to 8 and Comparative Examples 1 to 4 were prepared respectively, and prepared into 150mm*150mm*150mm standard cubic specimens for 28d compressive strength test, and prepared into 150mm*150mm*550mm standard prism specimens for 28d flexural strength test. The experimental equipment was an electronic universal testing machine, and the test adopted a three-point bending loading method.
[0123] Combustion calorific value: Referring to GB / T 14402-2007, take appropriate amounts of the thermal insulation lightweight concrete blocks of Examples 1 to 8 and Comparative Examples 1 to 4, grind them into powder, put the powder and benzoic acid into an oxygen bomb at a mass ratio of 1:2 for testing, and the experimental equipment is an oxygen bomb calorimeter with constant heat capacity.
[0124] Non-flammability test: Referring to GB / T 5464-2010, the thermal insulation lightweight concrete slurries of Examples 1 to 8 and Comparative Examples 1 to 4 were respectively prepared into cylinders with a height of 50 mm and a diameter of 45 mm. After curing for 28 days, the weight before the test was weighed M1, and then placed in a 750°C thermocouple heating combustion furnace for testing. After the fire lasted for 5 seconds, click to start the timing and record the fire time t1. After the open flame was extinguished, the continuous burning time t2 of the concrete block was recorded. The test was stopped after the temperature in the furnace reached equilibrium again, and the temperature rise T in the furnace was recorded. Finally, the concrete block after the test was taken out, the weight after the test was weighed M2, and the mass loss rate (%) was calculated. The mass loss rate (%) = (M1-M2) / M1*100%.
[0125] The above test results are shown in Table 1.
[0126] Table 1:
[0127]
[0128] Through Table 1, by comparing the test data of the embodiments and the comparative examples, we can see that the thermal insulation lightweight concrete of Examples 1 to 8 performs well in 28-day compressive strength and flexural strength, and the thermal insulation lightweight concrete of Examples 4 to 8 performs well in combustion calorific value and mass loss rate, which shows that the thermal insulation lightweight concrete of the present application has good mechanical properties, and further adding modified rice husk ash to the thermal insulation lightweight concrete can further improve the flame retardant properties.
[0129] Specifically combining the analysis of Example 1 and Comparative Examples 1 to 3, we can see that the thermal insulation lightweight concrete of Example 1 performs well in terms of 28-day compressive strength and flexural strength, which indicates that the use of the anti-floating agent provided by the present application in the thermal insulation lightweight concrete can effectively inhibit the agglomeration and floating of EPS particles in the concrete, effectively improve the dispersion of EPS particles in the concrete, ensure the uniformity and quality of the lightweight concrete, thereby effectively improving the mechanical properties of the thermal insulation lightweight concrete.
[0130] Specifically combining the analysis of Example 1 and Comparative Example 4, we can see that the thermal insulation lightweight concrete of Example 1 performs well in 28-day compressive strength and flexural strength, which indicates that the use of sepiolite fiber in thermal insulation lightweight concrete can effectively improve the mechanical properties of concrete, which further illustrates that there is a certain synergistic effect between sepiolite fiber and rice husk ash, and they have unique advantages in jointly improving the mechanical properties of thermal insulation lightweight concrete.
[0131] Specifically combining the analysis of Example 1 and Examples 4 to 8, we can see that the modified rice husk ash used in Examples 4 to 8 further enhances the flame retardant effect of the material. Specifically combining the analysis of Example 4 and Examples 6 to 8, we can see that the flame retardant effect of Example 4 is good, which indicates that diammonium dihydrogen phosphate, urea and polyethyleneimine can better cooperate to improve the flame retardant effect of thermal insulation lightweight concrete. The applicant specifically analyzed that this is due to the cooperation of diammonium dihydrogen phosphate, urea and polyethyleneimine, which can promote the formation of a dense coke layer, making the formed coke layer denser and more stable, thereby reflecting a good flame retardant effect.
[0132] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A thermal insulation lightweight concrete, characterized in that: The invention comprises the following components in parts by weight: 340-360 parts of cement, 85-95 parts of fly ash, 20-40 parts of rice husk ash, 250-270 parts of sand, 12-16 parts of EPS particles, 9-12 parts of expanded perlite particles, 5-8 parts of sepiolite fibers, 8-12 parts of anti-floating agent, 7-9 parts of water reducing agent and 165-180 parts of water, wherein the anti-floating agent is prepared by mixing corn starch, starch phosphate, polyethylene oxide and sodium lignin sulfonate.
2. The thermal insulation lightweight concrete according to claim 1, characterized in that: The mixing mass ratio of the corn starch, starch phosphate, polyethylene oxide and sodium lignin sulfonate is 1: (0.5-0.7): (0.3-0.5): (0.1-0.2).
3. The thermal insulation lightweight concrete according to claim 1, characterized in that: The mixing mass ratio of the corn starch, starch phosphate, polyethylene oxide and sodium lignin sulfonate is 1:0.6:0.4:0.
15.
4. The thermal insulation lightweight concrete according to claim 1, characterized in that: The preparation method of the anti-floating agent comprises: adding corn starch to 10 times the volume of water at 50-60° C., stirring evenly, then sequentially adding starch phosphate, polyethylene oxide and sodium lignin sulfonate, continuing stirring for 10-20 minutes, and drying to obtain the anti-floating agent.
5. The thermal insulation lightweight concrete according to claim 1, characterized in that: The EPS particles are continuous-grade particles with a particle size distribution between 5 and 8 mm, and the expanded perlite particles are continuous-grade particles with a particle size distribution between 2 and 4 mm.
6. The thermal insulation lightweight concrete according to claim 5, characterized in that: The mass ratio of the EPS particles to the expanded perlite particles is 15:
10.
7. The thermal insulation lightweight concrete according to claim 1, characterized in that: The method for preparing rice husk ash comprises: calcining rice husk at 450-500° C. for 30-45 minutes, and then grinding for 30-35 minutes to obtain rice husk ash.
8. The thermal insulation lightweight concrete according to claim 1, characterized in that: The rice husk ash is modified rice husk ash, and the preparation method of the modified rice husk ash comprises the following steps: Step s1: completely immerse the rice husk ash in a 2 mol / L sodium hydroxide solution, then treat it at a temperature of 90 to 100° C. for 1 to 1.2 hours, and then take it out and dry it; Step s2: at 120-130° C., 100 parts of dried rice husk ash are dispersed again in 5-10 times the volume of water, 8-12 parts of ammonium dihydrogen phosphate and 2-3 parts of polyethyleneimine are added, mixed and stirred for 1-2 hours, 10-15 parts of urea are added and stirring is continued for 1-2 hours, filtered, and dried at 100-120° C. to obtain modified rice husk ash.
9. The thermal insulation lightweight concrete according to any one of claims 1 to 8, characterized in that: The mass ratio of the rice husk ash to the sepiolite fiber is 30:
7.
10. A method for preparing a thermal insulation lightweight concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Take 20% to 25% of the formula amount of water, add anti-floating agent and stir evenly, then add EPS particles and expanded perlite particles, continue to stir evenly, then add rice husk ash and sepiolite fiber and stir evenly to obtain material 1; take cement, fly ash and sand and stir evenly to obtain material 2; take the remaining water, add water reducing agent and stir evenly to obtain material 3; Step 2: First mix material 2 and material 3 and stir evenly, then add material 1 and continue stirring evenly to obtain thermal insulation lightweight concrete.
Citation Information
Patent Citations
Superfine hollow microsphere thermal mortar and preparation method thereof
CN108484212A